Election Pledges in Multiparty Governments: When do Voters Accept Non-Fulfillment? - Ylisalo, Juha; Matthiess, Theres; Praprotnik, Katrin; Ennser-Jedenastik, Laurenz (Cambridge University Press, 2026)
Theories of representative democracy emphasize the importance of electoral pledges for informed voting and government accountability. Recent studies have highlighted citizens’ tendency to impose electoral punishments when parties fail to fulfill their pledges. However, conditions under which citizens consider non-fulfillment acceptable have received little attention. Specifically, multiparty government makes it less likely that an individual party fulfills its pledges, but whether citizens take such obstacles into account when evaluating the acceptability of non-fulfillment has remained largely untested. We theorize that both the coalition negotiation context and the negotiation outcome influence citizens’ evaluations. To test our hypotheses, we conducted two vignette experiments in Finland and Germany. The results revealed that, regardless of their opinion about the substance of a pledge, voters were more accepting of unfulfilled pledges when party or coalition characteristics created obstacles to fulfillment. The findings suggest that voters possess a nuanced understanding of the constraints of coalition government.